Odpowiedź :
4 - x² + 2xy - y² =
4 - (x² - 2xy + y²) =
4 - (x - y)² =
[2 + (x - y)] * [2 - (x - y)] =
(2 + x -y) * (2 - x + y)
Skorzystałam z dwóch wzorów skróconego mnożenia:
(a-b)²=a²-2ab+b²
a²-b²=(a-b)(a+b)
4 - (x² - 2xy + y²) =
4 - (x - y)² =
[2 + (x - y)] * [2 - (x - y)] =
(2 + x -y) * (2 - x + y)
Skorzystałam z dwóch wzorów skróconego mnożenia:
(a-b)²=a²-2ab+b²
a²-b²=(a-b)(a+b)
4 -x² + 2xy -y² =4 -(x-y)² = 2² - (x - y)² =
=[2 -(x-y)]*[2 +(x-y)] = (2 - x +y)*(2 +x - y)
=[2 -(x-y)]*[2 +(x-y)] = (2 - x +y)*(2 +x - y)